Results of a Study Comparing Planting Time and Biomass Yield of Green Manure Crops in the Steppe Zone of Mongolia - D., Onon; B., Amarsanaa (International Journal For Research In Agricultural And Food Science, 2021)
Due to the crop monoculture system which has been 60 years continuously played in a key role in the crop sector Mongolia, soil erosion and its fertility decline have been becoming one of the main pressing issues in all crop zones. The main solution of restoration of soil fertility in the steppe zone of Mongolia is not only to reduce bare fallow but also urgently need to apply green manure in all regions. Our study has focused on identifying the appropriate timing to cultivate green manure crops in the Eastern steppe region of Mongolia and to determine the convenient alternatives of crops with a high yield of biomass to use for green manure.We determined the most convenient time to use crop biomass for green manure is between 22-27th.July for the green manure crops cultivated on the 20th of May. For the crops cultivated on the 30th of May green manure time can be determined between 2-6th. August and for the crops cultivated on the 10th of June the convenient time would be between 10-13th.August. We prioritized the best option of the crop alternatives based on the 3 years average yield of green mass and concluded that field pea and oat mixture, Sudan grass, and fodder pea mixture can be one of the convenient options for green manure in the steppe zone of Mongolia. According to our study results, convenient alternatives with the highest root mass were yellow clover (27.5-60.5c/ha) and white lupine (27.5-61.4c/ha). In terms of biomass, the convenient alternatives with the highest biomass were the following crops planted on the 20th of May such as mixture of field pea and oat (82.5-112.2c/ha), fodder pea and Sudan grass (67.4-97.0c/ha), as well as Sudan grass (57.1-110.0c/ha. It is considered that in the steppe zone green manure crops can be used for green manure if the biomass of the crops can exceed 40c/ha. [1] The appropriate timing of the planting period should not be later than the 30th of May.